Dual IRE1 RNase functions dictate glioblastoma development. Issue 3 (8th January 2018) - Lhomond, Stéphanie; Avril, Tony; Dejeans, Nicolas; Voutetakis, Konstantinos; Doultsinos, Dimitrios; McMahon, Mari; Pineau, Raphaël; Obacz, Joanna; Papadodima, Olga; Jouan, Florence; Bourien, Heloise; Logotheti, Marianthi; et al.
Abstract: Proteostasis imbalance is emerging as a major hallmark of cancer, driving tumor aggressiveness. Evidence suggests that the endoplasmic reticulum (ER), a major site for protein folding and quality control, plays a critical role in cancer development. This concept is valid in glioblastoma multiform (GBM), the most lethal primary brain cancer with no effective treatment. We previously demonstrated that the ER stress sensor IRE1α (referred to as IRE1) contributes to GBM progression, through XBP1 mRNA splicing and regulated IRE1‐dependent decay (RIDD) of RNA. Here, we first demonstrated IRE1 signaling significance to human GBM and defined specific IRE1‐dependent gene expression signatures that were confronted to human GBM transcriptomes. This approach allowed us to demonstrate the antagonistic roles of XBP1 mRNA splicing and RIDD on tumor outcomes, mainly through selective remodeling of the tumor stroma. This study provides the first demonstration of a dual role of IRE1 downstream signaling in cancer and opens a new therapeutic window to abrogate tumor progression. Synopsis: The IRE1 arm of the Unfolded Protein Response (UPR) plays a major role in cancer development. Dissecting IRE1 signals in human glioblastoma tumors, primary and established cell lines reveals the dual role of XBP1 mRNA splicing and RIDD in tumor aggressiveness. GBM tumors cluster into two groups exhibiting low or high IRE1 activity. XBP1s elicits pro‐tumorigenic signals and promotes angiogenesis and macrophage recruitment to the tumor. RIDD dampens angiogenesis and tumor cell migration. Patients bearing tumors with high XBP1s low RIDD features show lower survival than those with low XBP1s high RIDD, thereby providing potential therapeutic avenues. Abstract : The IRE1 arm of the Unfolded Protein Response (UPR) plays a major role in cancer development. Dissecting IRE1 signals in human glioblastoma tumors, primary and established cell lines reveals the dual role of XBP1 mRNA splicing and RIDD in tumor aggressiveness.